Dynamics of hierarchical conflict in higher education: What does the literature tell us about performance and well-being? - Putu Gede Subhaktiyasa; Arisusana, I Made; Wahyudi, Hendro; Sumaryani, N. Putri (JURUSAN MANAJEMEN PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI GORONTALO, 2024)
Hierarchical conflict in higher education institutions can affect the performance and welfare of lecturers and administrative staff, but in-depth studies on the impact and conflict management strategies still need to be explored. This study aims to provide an understanding of the impact of hierarchical conflict on the performance and well-being of lecturers and administrative staff and effective strategies for managing conflict. This study uses a literature review method, which examines findings from relevant literature with a content analysis approach. The results indicate that hierarchical conflict can potentially reduce academic productivity and operational efficiency and increase staff stress and burnout. However, in some cases, conflict can also spark innovation and collaboration. Effective conflict management strategies include managerial, cultural, and structural approaches. The findings contribute to developing conflict management policies and practices in higher education institutions and provide theoretical insights to guide future research.